Modelling transport decarbonisation pathways in Vietnam: Synergies and trade-offs in supporting the energy transition - Nuzulia Fajriningrum; Leonhard Hofbauer; Naomi Tan; Steve Pye (Energy Strategy Reviews)
Transport is the second-largest energy using sector in Vietnam and is projected to have the highest energy and emissions growth in future years. This paper explores options for decarbonising Vietnam's transport sector using a mixed-methods approach, including qualitative scenario design and quantitative energy system modelling. Three strategies are explored - modal shifting, fuel switching, and improving fuel economy, alongside Vietnam's 8th Power Development Plan to identify alternative pathways to reduce transport emissions. Further scenarios are constructed to assess the wider implications of low-carbon mobility in fostering Vietnam's energy transition towards climate mitigation targets.We find that improving fuel economy is the most efficient transport-focused pathway to decouple emission and energy demand from mobility growth, while modal shift is crucial for reducing traffic congestion and carbon dioxide emission. Fuel switching to electric vehicles must be undertaken in parallel with efforts to lower carbon intensity in power generation, to avoid the risk of indirect emissions. Combining all three transport decarbonisation strategies with higher renewables and a carbon tax can fulfil Vietnam's unconditional Nationally Determined Contributions target by 2030. While the co-benefits of carbon dioxide abatement and fuel import avoidance will improve Vietnam's energy security and environmental sustainability, the study suggests that the risks of trade-offs in land-use implications and rising future electricity costs must be considered to support a just and equitable energy transition in Vietnam.